Role of Estrogen Receptors and G Protein-Coupled Estrogen Receptor in Regulation of Hypothalamus–Pituitary–Testis Axis and Spermatogenesis - Chimento, Adele; Sirianni, Rosa; Casaburi, Ivan; Pezzi, Vincenzo (Frontiers in Endocrinology, 2014)
Male reproductive function is under the control of both gonadotropins and androgens through a negative feedback loop that involves the hypothalamus, pituitary and testis known as hypothalamus-pituitary-gonadal axis (HPG). Indeed, also estrogens play an important role in regulating HPG axis but the relative contribution to the inhibition of gonadotropins secretion exerted by the amount of estrogens produced within the hypothalamus and/or the pituitary or by the amount of circulating estrogens are still ongoing. Moreover, it is known that maintenance of spermatogenesis is controlled by gonadotrophins and testosterone, the effects of which are modulated by a complex network of locally produced factors, including estrogens. Physiological effects of estrogens are mediated by the classical nuclear estrogen receptor alpha (ESR1) and estrogen receptor beta (ESR2), which mediate both genomic and rapid signaling events. In addition, estrogens induce rapid non-genomic responses through a membrane-associated G protein-coupled receptor (GPER). Ours and other studies reported that, in the testis, GPER is expressed in both normal germ cells and somatic cells and it is involved in mediating the estrogen action in spermatogenesis controlling proliferative and/or apoptotic events. Interestingly, GPER expression has been revealed also in hypothalamus and in pituitary. However, its role in mediating estrogen rapid actions in this context is under investigation. Recent studies indicate that GPER is involved in modulating GnRH release as well as gonadotropins secretion. In this review, we will summarize the current knowledge concerning the role of estrogen/estrogen receptors (ERs) molecular pathways in regulating GnRH, FSH and LH release at hypothalamic and pituitary level in male as well as in controlling specific testicular functions such as spermatogenesis, focusing our attention mainly on estrogen signaling mediated by GPER.